BIMBINGAN KOLABORATIF MGMP SEKOLAH SEBAGAI ALTERNATIF SUPERVISI AKADEMIK YANG EFEKTIF DI SMP NEGERI 5 LAHAT - ABDUL RAHIM (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2023)
School action research (PTS) has been carried out with the intention of exploring the benefits of collaborative mentoring in school MGMPs, forming professional learning communities, and achieving effective academic supervision. The research was conducted at SMP Negeri 5 Lahat with a total of 15 teachers, starting from January to February 2022. This research used collaborative guidance on the school's MGMP through two cycles. The factors observed included teacher activity, teacher interest attitudes, school MGMP products, and student interest attitudes. The results of the research cycle II generally experienced an increase when compared to cycle I. The teacher's activity in cycle II was on average good 43% and very good 36.67% while cycle I was quite average 42% and good 47%. The attitude of the teacher's interest after the second cycle of activities experienced a very good increase on average 55.99%, and 33.13% good, while the first cycle was very good on average 40.59%, and 43.24% good. The results of the school MGMP in cycle II for the syllabus averaged 85.36% complete and in accordance with the guidelines, while in cycle I it was only 30.93%, as well as the RPP in cycle II, which averaged 78.23% according to the guidelines. and complete, whereas in cycle I it was only 54.69%. Another aspect in cycle II is the implementation of the learning design in the teacher's class facilitating active students including the very good category average 13.31% and the good category average 36.43% and student learning activities including the good category average 51.11% and very good average 19.66%. Students' attitudes and interests after the learning process were very good on average 38.73% and good on average 33.26%. Based on the results of research in cycle II MGMP/school community collaborative guidance can improve the quality and quantity of learning designs and the implementation of educational learning. This is accompanied by increased activity, attitude, interest of teachers and students. This academic supervision becomes effective through collaborative guidance of the MGMP/school community and the formation of a professional learning community ABSTRAKPenelitian tindakan sekolah (PTS) telah dilaksanakan dengan maksud untuk mengetahui manfaat bimbingan kolaboratif di MGMP sekolah, membentuk komunitas pembelajaran profesional, dan mencapai supervisi akademik yang efektif. Penelitian dilaksanakan di SMP Negeri 5 Lahat dengan jumlah total guru sebanyak 15 orang, dimulai bulan Januari sampai bulan Februari 2022. Penelitian ini menggunakan bimbingan kolaboratif pada MGMP sekolah melalui dua siklus. Faktor-faktor yang diamati meliputi aktifitas guru, sikap minat guru, produk MGMP sekolah, dan sikap minat siswa. Hasil penelitian siklus II umumnya mengalami peningkatan jika dibandingkan dengan siklus I. Aktifivtas guru pada siklus II rata-rata baik 43% dan sangat baik 36,67% sedangkan siklus I katagori cukup rata-rata 42% dan baik 47%. Sikap minat guru setelah kegiatan siklus II mengalami peningkatan sangat baik rata-rata 55,99%, dan baik 33,13%, sedangkan disiklus I sangat baik rata-rata 40,59%, dan baik 43,24%. Produk hasil MGMP sekolah pada siklus II untuk silabus rata-rata 85,36% lengkap dan sesuai rambu-rambu, sedangkan siklus I hanya 30,93%, begitu pula dengan RPP pada siklus II rata-rata 78,23% sesuai rambu-rambu dan lengkap, sedangkan pada siklus I hanya 54,69%. Aspek lainnya pada siklus II implementasi rancangan pembelajaran di kelas guru memfasilitasi siswa aktif termasuk katagori sangat baik rata-rata 13,31% dan katagori baik rata-rata 36,43% serta aktivitas belajar siswa termasuk katagori baik rata-rata 51,11% dan sangat baik rata-rata 19,66%. Sikap dan minat siswa setelah proses pembelajaran sangat baik rata-rata 38,73% dan baik rata-rata 33,26%. Berdasarkan hasil penelitian pada siklus II bimbingan kolaboratif MGMP/komunitas sekolah dapat meningkatkan kualitas dan kuantitas rancangan pembelajaran serta implementasi pembelajaran yang mendidik. Hal ini disertai juga dengan meningkatnya aktivitas, sikap, minat guru dan siswa. Supervisi akademik ini menjadi efektif melalui bimbingan kolaboratif MGMP/komunitas sekolah dan terbentuknya komunitas pembelajaran profesional